Construcción de un banco para prácticas de automatización y control industria, con autómatas programables. - Fernández Vallejo, Fernando Patricio (2013)
The PLC automation is used today as a technology for industrial processes exist in the market a wide range of models of automata. Therefore is necessary that deepens every day in the study of these new technologies, also know the most common programming languages for existing brands and best known as Siemens, Osrom, Unitronics, Koyo, Lg, among others. By requiring supervision must also become familiar with the software thus Scada to conduct monitoring of processes within an industrial plant or remotely. With this work we want to show the whole process of design, construction, installation, programming, monitoring and control of a process by means of a bank of industrial automation PLC, which allows the student electromechanical National University of Loja involved in practical form in knowledge and development of these technologies, present in current industrial processes.